Towards Paraconsistent Engineering - Akama, Seiki (Intelligent Systems Reference Library, 2016)
This book presents a collection of contributions from related logics to applied paraconsistency. Moreover, all of them are dedicated to Jair Minoro Abe,on the occasion of his sixtieth birthday. He is one of the experts in Paraconsistent Engineering, who developed the so-called annotated logics. The book includes important contributions on foundations and applications of paraconsistent logics in connection with engineering, mathematical logic, philosophical logic, computer science, physics, economics, and biology. It will be of interest to students and researchers, who are working on engineering and logic. .